Dangers of weights? Rationality of the weights in the interpretation of fundamental rights - Portocarrero Quispe, Jorge Alexander (2016)
The aim of this article revolves around the identification of the alleged dangers  that the weighting procedure would entail and if indeed these hazards are due to weighting own or if instead derived from the intentions of the legal operator. This problem reflects the central question of this article: are the dangers of internal weighting structure or rather external to it? The thesis will be developed in subsequent is that the dangers of weighting are external to it and depend on the subjectivity of the legal operator, in some cases, not looking necessarily direct their argument towards a correction of justice, but interests or personal circumstances. The article will address therefore the main criticisms of the weighting procedure as rational interpretation of rules as a matter of principle, that is, fundamental rights and collective goods. To the extent that critical approaches are addressed, it will provide an answer to them to assess whether indeed it right in questioning the r